Shoots induction of axillary buds in blueberries (Vaccinium corymbosum L.) in vitro with the addition of BAP and IBA - Restanto, Didik Pudji; Budha, Al Sura Tri; Prayoga, Mohammad Candra; Slameto, Slameto; Khozin, Mohammad Nur (Biogenesis: Jurnal Ilmiah Biologi, 2024)
Blueberry Vaccinium corymbosum L. is a fruit plant that has high economic value and many benefits. Blueberries in Indonesia are not yet in great demand so domestic needs are still met by imports. Conventional blueberry propagation is done using stem cuttings. The disadvantages of conventional propagation are that seedling growth is slow, requires a large source of planting material, and is ineffective. The aim of the research was to determine the effect of the combination of BAP and IBA hormones on the induction of axillary shoots in effective in vitro propagation of blueberries. The explants used were axillary buds of blueberry, sterilized using fungicide, bactericide, bayclin, sodium hypochlorite and alcohol. The research design used a completely randomized design (CRD) with a combination of BAP and IBA hormones. The BAP hormone consists of three concentrations, namely 0.5, 1.0, and 1.5 mg/L. The IBA hormone consists of three concentrations, namely 0, 0.1, and 0.2 mg/L. Based on research results, the combination treatment of BAP and IBA succeeded in inducing shoots, but was not able to induce roots. The BAP 0.5 mg/L treatment showed the best results with a shoot emergence rate of 4.33 weeks, shoot height of 1.68 cm, number of shoots 1.67, and number of leaves 12.67. The findings of this study highlight the potential of BAP and IBA hormone combinations in accelerating blueberry shoot induction, offering an alternative propagation method that could support domestic production and reduce dependence on imports.